Extracellular signal‐regulated kinase phosphorylation in forebrain neurones contributes to osmoregulatory mechanisms. (6th March 2014) - Dine, Julien; Ducourneau, Vincent R. R.; Fénelon, Valérie S.; Fossat, Pascal; Amadio, Aurélie; Eder, Matthias; Israel, Jean‐Marc; Oliet, Stéphane H. R.; Voisin, Daniel L.
Abstract : Key points: The mechanisms of osmotically induced vasopressin secretion from the hypothalamic magnocellular neurosecretory cells, which is crucial for body fluid homeostasis, are not yet fully understood. Extracellular signal‐regulated protein kinases (ERK) are mitogen‐activated protein kinases that transduce extracellular stimuli into intracellular post‐translational and transcriptional responses and might be involved in the regulation of vasopressin release in response to changes in osmolality. We found that ERK was dose‐dependently activated (phosphorylated) in the rat osmosensitive forebrain regions, including magnocellular neurosecretory cells, by increases in osmolality induced by hypertonic solutions. Inhibition of ERK phosphorylation reduced hypertonically induced activation of osmosensitive forebrain neurones and vasopressin release. Our results identify ERK activation as a new element contributing to the osmoregulatory mechanisms of vasopressin release. Abstract: Vasopressin secretion from the magnocellular neurosecretory cells (MNCs) is crucial for body fluid homeostasis. Osmotic regulation of MNC activity involves the concerted modulation of intrinsic mechanosensitive ion channels, taurine release from local astrocytes as well as excitatory inputs derived from osmosensitive forebrain regions. Extracellular signal‐regulated protein kinases (ERK) are mitogen‐activated protein kinases that transduce extracellular stimuli into intracellular post‐translational and transcriptional responses, leading to changes in intrinsic neuronal properties and synaptic function. Here, we investigated whether ERK activation (i.e. phosphorylation) plays a role in the functioning of forebrain osmoregulatory networks. We found that within 10 min after intraperitoneal injections of hypertonic saline (3 m, 6 m ) in rats, many phosphoERK‐immunopositive neurones were observed in osmosensitive forebrain regions, including the MNC containing supraoptic nuclei. The intensity of ERK labelling was dose‐dependent. Reciprocally, slow intragastric infusions of water that lower osmolality reduced basal ERK phosphorylation. In the supraoptic nucleus, ERK phosphorylation predominated in vasopressin neurones vs . oxytocin neurones and was absent from astrocytes. Western blot experiments confirmed that phosphoERK expression in the supraoptic nucleus was dose dependent. Intracerebroventricular administration of the ERK phosphorylation inhibitor U 0126 before a hyperosmotic challenge reduced the number of both phosphoERK‐immunopositive neurones and Fos expressing neurones in osmosensitive forebrain regions. Blockade of ERK phosphorylation also reduced hypertonically induced depolarization and an increase in firing of the supraoptic MNCs recorded in vitro . It finally reduced hypertonically induced vasopressin release in the bloodstream. Altogether, these findings identify ERK phosphorylation as a new element contributing to the osmoregulatory mechanisms of vasopressin release.